The Lake Petén Itzá Scientifi c Drilling Project - Daniel Ariztegui; Mark Brenner; Flavio S. Anselmetti; David A. Hodell (Scientific Drilling, 2006)
Polar ice cores provide us with high-resolution records of past climate change at high latitudes on both glacial-to-interglacial and millennial timescales. Paleoclimatologists and climate modelers have focused increasingly on the tropics, however, as a potentially important driver of global climate change because of the region’s role in controlling the Earth’s energy budget and in regulating the water vapor content of the atmosphere. Tropical climate change is often expressed most strongly as variations in precipitation, and closed-basin lakes are sensitive recorders of the balance between precipitation and evaporation. Recent advances in fl oating platformsand drilling technology now offer the paleolimnological community the opportunity to obtain long sediment records from lowland tropical lakes, as illustrated by the recent successful drilling of Lakes Bosumtwi and Malawi in Africa (Koeberl et al., 2005; Scholz et al., 2006). Tropical lakes suitable for paleoclimatic research were sought in Central America to complement the African lake drilling. Most lakes in the Neotropics are shallow, however, and these basins fell dry during the Late Glacial period because the climate in the region was more arid than today. The search for an appropriate lake to study succeeded in 1999 when a bathymetric survey of Lake Petén Itzá, northern Guatemala, revealed a maximum depth of 165 m, making itthe deepest lake in the lowlands of Central America (Fig. 1 ).Although the lake was greatly reduced in volume during the Late Glacial period, the deep basin remained submerged and thus contains a continuous history of lacustrine sediment deposition. A subsequent seismic survey of Lake Petén Itzá in 2002 showed a thick sediment package overlying basement, with several subbasins containing up to 100 m of sediment (Anselmetti et al., 2006).